Clinicians views of the training, use and maintenance of phonetic transcription in speech and language therapy - the Irish perspective - Yanushevskaya, Irena (My University, 2021)
Background: Phonetic transcription is an essential skill for a practicing Speech and Language Therapist (SLT). Maintaining transcription skills and adhering to good transcription practice is important for correct assessment of speech disorders. This study explores clinicians' views of the training, use and maintenance of phonetic transcription by SLTs in Ireland. To date, this research topic has not been carried out in Ireland. Methods: An online survey was conducted using a questionnaire based on Knight et al. (2018), with permission. The questionnaire contained 39 questions collecting both quantitative and qualitative data, and included some modifications to fit the Irish context. Eighteen participants completed the survey. Quantitative data was analysed using descriptive statistics. Qualitative data was analysed using content analysis. Results: For 88% of participants phonetic transcription was required for their current role; 50% of participants use it often or all the time. 67% of participants are confident/very confident when using transcription. Transcription is used mainly for assessment (100%) and reassessment (82%). Broad transcription is the most commonly used (67% of SLTs use broad transcription only, 22% use a mixture of broad and narrow transcription). Only 28% of SLTs feel supported in workplace to maintain their transcription skills. Only 6% reported having attended refresher courses in phonetics, but the majority (67%) expressed interest in attending such courses. Revision of college notes and internet resources are used by 88% of the participants as a means to maintain transcription skills. Conclusion: The results suggest that there is a need for more practical elements and resources available to students learning transcription. As the majority of participant SLTs expressed an interest in attending refresher courses in transcription, it is important that educators, managers and regulatory bodies collaborate to support SLTs in maintaining their transcription skills. The findings are compared to similar studies (Knight et al, 2018; Nelson et al, 2019).
ICPLA 2021
PRESENTED
Glasgow,UK